Enhanced publications : linking publications and research data in digital repositories - Woutersen-Windhouwer, Saskia; Vernooy-Gerritsen, Marjan (Trends in research information management., 2009)
"The traditional publication will be overhauled by the ''Enhanced Publication''. This is a publication that is enhanced with research data, extra materials, post publication data, and database records. It has an object-based structure with explicit links between the objects. In this book a state-of-the-art overview is given of the structural elements of an Enhanced Publication, as well as publication models, interrelationship and repository issues. The use of Enhanced Publications evokes questions on object models and functionalities. In-depth study is made of these subjects. More practically, a sample is given of datasets together with a demonstrator-project. In the final section, this book deals with long-term preservation issues, linking to the developments of digital repositories that are studied in other books in this series"--EBL.